2015
DOI: 10.1111/roiw.12191
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at Intergenerational Mobility in Germany Compared to the U.S

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
7
25
0
Order By: Relevance
“…This is in contrast to what has been found in previous studies of other countries using standard CQR (Bratsberg et al (2005) for Norway, Eide and Showalter (1999) and Palomino et al (2018) for the USA and Grawe (2004) for Canada). Our findings are, however, in line with recent studies from Björklund et al (2012) for Sweden and Schnitzlein (2016) for Germany and the USA. Given the sensitivity of estimates of the IGE across the distribution to the age the son is observed, we focus on a lifetime estimate of IGE, considering average earnings across the observed part of the lifecycle from ages 26 to 42.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…This is in contrast to what has been found in previous studies of other countries using standard CQR (Bratsberg et al (2005) for Norway, Eide and Showalter (1999) and Palomino et al (2018) for the USA and Grawe (2004) for Canada). Our findings are, however, in line with recent studies from Björklund et al (2012) for Sweden and Schnitzlein (2016) for Germany and the USA. Given the sensitivity of estimates of the IGE across the distribution to the age the son is observed, we focus on a lifetime estimate of IGE, considering average earnings across the observed part of the lifecycle from ages 26 to 42.…”
Section: Resultssupporting
confidence: 94%
“…These findings are in contrast to studies from the USA, Norway and Canada that find a decreasing intergenerational relationship as they move up the earnings distribution based on the problematic, in this context, conditional quantile regression technique. They are however consistent with literature in the UK about the strong role of family background in access to and progression within top jobs (Macmillan 2009;Macmillan et al 2015;Laurison and Friedman 2016), persistence in jobless spells across generations (Macmillan 2014;Gregg et al 2018) and patterns of IGEs across sons' earnings from Björklund et al (2012) for Sweden and Schnitzlein (2016) for both Germany and the USA.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The Importance of Family Background for Low, Middle, and High Academic Performance Although previous research on the intergenerational transmission of educational advantage has neglected that the relationship between parental and children's education may vary for children with different levels of academic performance, studies from economics have found intergenerational income mobility to vary across the distribution of offspring's income (Eide and Showalter 1999;Grawe 2004;Raitano, Vittori, and Vona 2016;Schnitzlein 2016). Similar nonlinearities may exist in educational mobility.…”
Section: Background and Theoretical Considerationsmentioning
confidence: 99%